PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE (STAD) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS MATERI PROSES ALAM ENDOGEN TERHADAP PEMBENTUKAN MUKA BUMI - SULISTYANI SULISTYANI (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2022)
Judging from the acquisition of student learning outcomes that have not been satisfactory, so it is necessary to apply a learning method to improve student learning outcomes, the researcher is interested in applying the STAD method to improve student learning outcomes. This research is a classroom action research with the hope that this method can increase student motivation and learning outcomes. It consists of several main aspects of treatment and observation, namely the use of the STAD type cooperative learning model. The problem in this study is whether the application of the STAD type cooperative learning model can increase the motivation and learning outcomes of class VIIIB students of SMPN 4 Cibarusah. The research was conducted at SMPN 4 Cibarusah, involving 38 students consisting of 17 boys and 21 girls who were enrolled in the 2022/2023 academic year. The target of this research was class VIII B students. The data obtained were in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis it was found that the increase from 44 in pre-cycle learning outcomes to 57.3 in cycle I, then increased to 81.05 in cycle II. While the value of students' absorption also increased from 44% in pre-cycle to 57.3% in cycle I, then increased to 81.05% in cycle II. Learning completeness also increased from 13% in pre-cycle learning outcomes, rose to 24% in cycle I, then increased to 100% in cycle II. The conclusion from this study is that the Cooperative Approach Type STAD can have a positive effect on increasing motivation and learning outcomes for class VIII.B students of SMP Negeri 4 Cibarusah, and this learning model can be used as an alternative to social studies learning. Therefore, this research was compiled with the title Implementation of the Learning Method Approach (STAD) to Increase Motivation and Learning Achievement in Social Studies Material Endogenous Natural Processes on the Formation of the Earth at SMPN 4 Cibarusah in the 2022/2023 Academic Year. ABSTRAKDilihat dari perolehan hasil belajar siswa yang belum memuaskan, sehingga diperlukan penerapan sebuah metode pembelajaran untuk meningkatkan hasil belajar siswa maka peneliti tertarik untuk menerapkan metode STAD untuk meningkatkan hasil belajar siswa. Penelitian ini adalah penelitian tindakan kelas dengan harapan metode ini dapat meningkatkan motivasi dan hasil belajar siswa. Terdiri beberapa aspek perlakuan dan pengamatan utama yaitu Penggunaan Model Pembelajaran kooperatif tipe STAD. Permasalahan dalam penelitian ini adalah apakah dengan penerapan model pembelajaran kooperatif tipe STAD dapat meningkatkan motivasi dan hasil belajar siswa kelas VIIIB SMPN 4 Cibarusah. Penelitian dilaksanakan di SMPN 4 Cibarusah ,melibatkan 38 orang siswa terdiri atas 17 orang laki-laki dan 21 orang perempuan yang terdaftar pada tahun ajaran 2022/2023. Sasaran penelitian ini adalah siswa kelas VIII B. Data yang diperoleh berupa hasil tes formatif, lembar observasi kegiatan belajar mengajar. Dari hasil analisis didapatkan bahwa peningkatan dari 44 pada hasil belajar prasiklus menjadi 57,3 pada siklus I, kemudian meningkat menjadi 81,05 pada siklus II. Sedangkan nilai daya serap siswa juga mengalami peningkatan dari 44% pada prasiklus meningkat menjadi 57,3 % pada siklus I, kemudian meningkat menjadi 81,05 % pada siklus II. Ketuntasan belajar juga mengalami peningkatan dari 13% pada hasil belajar prasiklus, naik menjadi 24 % pada siklus I, kemudian meningkat menjadi 100% pada siklus II. Simpulan dari penelitian ini adalah Pendekatan Kooperatif Tipe STAD dapat berpengaruh positif terhadap peningkatan Motivasi dan Hasil belajar siswa kelas VIII.B SMP Negeri 4 Cibarusah, serta model pembelajaran ini dapat digunakan sebagai salah satu alternatif pembelajaran IPS. Oleh karena itu disusunlah penelitian ini dengan judul Pelaksanaan Pendekatan Metode Pembelajaran (STAD) Untuk Meningkatkan Motivasi Dan Prestasi Belajar IPS Materi Proses Alam Endogen Terhadap Pembentukan Muka Bumi di SMPN 4 Cibarusah Tahun Pelajaran 2022/2023.